The emperor's children - Messud, Claire, 1966- (New York : Vintage Books, 2007)
Friends at Brown University, Marina, Danielle, and Julius are still looking to make their marks as they approach their 30s. Marina lives with her celebrated parents on the Upper West Side while trying to complete her book. TV producer Danielle's success is due to the puff pieces she churns out. Freelance critic Julius can barely make ends meet. Into this mix comes Bootie, Marina's college droupout cousin, who is just the catalyst the three friends need to start making siginificant changes in their lives.
Keywords: Friendship -- Fiction; New York (N.Y.) -- Fiction